Abdominal Ultrasonogram in Typhoid Fever: A Useful Diagnostic Tool (Journal of Paediatric Surgeons of Bangladesh, 2016)
Objectives: To See the use of abdominal ultrasonogrphic in the diagnosis of Typhoid fever.Materials and Methods: This cross sectional study on enteric fever was carried out during the period of July 2008 to June 2009 on 30 patients between 2 months 12 years of age of either sex admitted with the clinical diagnosis of enteric fever having positive hemoculture for Salmonella typhi or paratyphi and or significant Widal test. Abdominal USG was done at Centre for Nuclear Medicine and Ultrasound, Bangladesh atomic energy commission, Sir Salimullah Medical College & Mitford Hospital.Result: On ultrasonogram, hepatomegaly observed in 93.3% cases, splenomegaly in 53.3% cases, thickened bowel wall in 46.7% cases, enlarged mesenteric lymph node in 63.3% cases and 30% cases showed gall bladder changes. Ultrasonogram was done on first week of fever in 33.3% cases, on second week in 43.3% cases and third week in 23.3% cases. Out of them ultrasonogram done on first day of admission in 6.6% cases, on second day in 80% cases and third day in 13.3% cases. In first week the bowel wall thickening found in 10% cases, lymph node enlargement in 23.3% cases and gall bladder changes in 3.3% cases, in second week the bowel wall thickening found in 23.3% cases, lymph node enlargement in 26.6% cases and gall bladder changes in 20% cases, in third week the bowel wall thickening found in 13.3% cases, lymph node enlargement in 13.3% cases and gall bladder changes in 6.6% cases. Sonologic findings of bowel wall thickening, lymph node enlargement and gall bladder changes found in 23.33% cases in 1st week, 33.33% cases in 2nd week and 13.33% cases in 3rd week.Conclusion: In endemic areas like Bangladesh ultrasound findings of hepatomegaly, splenomegaly, mesenteric lymphadenopathy, bowel wall thickening, gall bladder changes are useful diagnostic features of typhoid fever.J. Paediatr. Surg. Bangladesh 5(2): 58-63, 2014 (July)